Does the song really remain the same? 'The Windmills of Your Mind' as narrational vehicle in The Thomas Crown Affair (1968 and 1999). Issue 2 (1st October 2014) - Bennett, Marie
Despite the charisma of its stars, Steve McQueen and Faye Dunaway, the original version of The Thomas Crown Affair (Jewison, 1968) is not thought of as a classic film of its era. As a consequence, it is generally best remembered less for its plot than for its use of novel split screen images, the infamous chess game scene, and its Oscar-winning song, 'The Windmills of Your Mind', performed by Noel Harrison. The song is heard during the film's opening titles, but also features as non-diegetic underscore during a scene in which Crown (McQueen) flies a glider part way through the film. Various scholars suggest that 'The Windmills of Your Mind's inclusion is as an interpolated song, i.e., that it has no particular connection to the film's storyline. In contrast, I argue that the song's music and lyrics do serve a narrative function, and that my claim is reinforced through its inclusion in the 1999 remake, which features Pierce Brosnan and Rene Russo in the leading roles. On this occasion, the song appears to be included as an homage to the original version; it is performed by another Englishman, Sting, and it is heard over the closing credits as an evocative reminder of the earlier film.